The Effectiveness of Memory Strategies to Improve Students' Speaking Skills - Arum Putri Rahayu; Masriatus Sholikhah (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
This research studies the memory strategies used by the second semester STAI Ma’arif Magetan students to improve their speaking skills through involvement in English vocabulary. The purpose of this research is to find out the types of strategies and students' preferences in using strategic memory to improve their speaking skills. The data consists of memory strategies used by STAI Ma’arif Magetan students. The data source consisted of 30 second semester students. The memory strategy questionnaire was carried out for the data collection process. Data analysis was carried out using several steps such as data reduction, displaying data, and drawing conclusions. The research results showed: (1) students used ten indicators of strategic memory (grouping, associating, placing new words into a context, using images, semantic solvers, using keywords, representing sounds in memory, structural displays, using physical responses or sensation, and using mechanical techniques); (2) students' preferences in using memory strategies to place new words into context.